2011
DOI: 10.1371/journal.pgen.1002137
|View full text |Cite
|
Sign up to set email alerts
|

Translation Reinitiation Relies on the Interaction between eIF3a/TIF32 and Progressively Folded cis-Acting mRNA Elements Preceding Short uORFs

Abstract: Reinitiation is a gene-specific translational control mechanism characterized by the ability of some short upstream uORFs to retain post-termination 40S subunits on mRNA. Its efficiency depends on surrounding cis-acting sequences, uORF elongation rates, various initiation factors, and the intercistronic distance. To unravel effects of cis-acting sequences, we investigated previously unconsidered structural properties of one such a cis-enhancer in the mRNA leader of GCN4 using yeast genetics and biochemistry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(172 citation statements)
references
References 40 publications
7
165
0
Order By: Relevance
“…[52][53][54] Further, eIF3g was found to interact with uS3 and uS10 located in the 40S subunit beak and head, respectively. 55 RpuS10 harbors an eukaryote-specific Nterminal extension that occupies part of the head region where eIF3g is believed to reside.…”
Section: E999576-6mentioning
confidence: 94%
“…[52][53][54] Further, eIF3g was found to interact with uS3 and uS10 located in the 40S subunit beak and head, respectively. 55 RpuS10 harbors an eukaryote-specific Nterminal extension that occupies part of the head region where eIF3g is believed to reside.…”
Section: E999576-6mentioning
confidence: 94%
“…This aberrant termination/ribosome-release cycle permits reinitiation to occur at a subsequent downstream AUG codon. It is likely that only the 40S ribosome remains attached to the mRNA following termination at uORF1 and that the 40S retains some bound translation factors, including eIF3 (Szamecz et al 2008;Munzarova et al 2011;Peter et al 2015). The 40S lacks eIF2, as this factor was released at AUG recognition ( Figure 9B, step iia) and prior to 60S joining ( Figure 9B, step iib).…”
Section: Gcn4mentioning
confidence: 99%
“…The 59 reinitiation enhancer region (59 RER) was shown to interact with eIF3a bound to the 40S (Szamecz et al 2008). The 59 RER contains four distinct elements, two of which are important for eIF3a binding (Munzarova et al 2011). Based on its ribosome-binding properties, eIF3a bridges the mRNA interaction to the 40S protein Rps0A located near the 40S mRNA exit channel (Szamecz et al 2008).…”
Section: Gcn4mentioning
confidence: 99%
“…This repressive effect of uORFs can be, however, alleviated under specific conditions, such as various types of stress, in order to boost expression of some regulatory uORFcontaining mRNAs that help the cell to cope with sudden environmental changes. It has been shown that the efficiency of REI depends on four main factors: (i) time required for uORF translation, which is determined by the relative length of uORF and the translation elongation rate; (ii) its 5 ′ and 3 ′ flanking sequences, which contain specific cis-acting features with poorly understood molecular roles; (iii) translation initiation factors (eIFs) involved in the primary initiation event such as the eIF3 and eIF4F complexes, which are believed to remain associated with the ribosome throughout the short elongation as well as termination and recycling phases; and (iv) its distance to the next open reading frame, which determines the likelihood of acquisition of the new TC by the posttermination 40S ribosome that has resumed scanning (Kozak 1987;Dever et al 1992;Pöyry et al 2004;Szamecz et al 2008;Cuchalová et al 2010;Roy et al 2010;Munzarová et al 2011). …”
Section: Introductionmentioning
confidence: 99%